2016
DOI: 10.3892/etm.2016.3902
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of sheep kidney-derived mesenchymal stem cells

Abstract: The aim of the present study was to isolate, culture and characterize sheep metanephric mesenchymal stem cells (MMSCs). The MMSCs were isolated from the kidney tissue of six-week-old sheep fetus. This study investigated whether primary MMSCs could be grown for 26 passages and expressed Oct-4, which is involved in the self-renewal of undifferentiated pluripotent stem cells. The MMSCs also expressed the renal lineage marker gene PAX2, and mesenchymal cell marker genes CD44, FN1 and VIM. Expression of these genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This study clearly showed that the application of Bambusa tulda decreased mesenchymal stem cells. In previous reports, mesenchyamal stromal cells are treated with individual and mixtures of crude herbal extracts, as well as with purified compounds from herbal extracts, to investigate the mechanisms and effects of differentiation of stem cells [5,[12][13][14][15]. Er-Xian Decoction, a traditional Chinese herbal formula widely used for postmenopausal osteoporosis treatment is reported to stimulate osteoblastic differentiation of bone mesenchymal stem cells in ovariectomized mice by rescuing several gene expressions that were dysregulated including osteocalcin [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study clearly showed that the application of Bambusa tulda decreased mesenchymal stem cells. In previous reports, mesenchyamal stromal cells are treated with individual and mixtures of crude herbal extracts, as well as with purified compounds from herbal extracts, to investigate the mechanisms and effects of differentiation of stem cells [5,[12][13][14][15]. Er-Xian Decoction, a traditional Chinese herbal formula widely used for postmenopausal osteoporosis treatment is reported to stimulate osteoblastic differentiation of bone mesenchymal stem cells in ovariectomized mice by rescuing several gene expressions that were dysregulated including osteocalcin [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ginkgo biloba extract promotes osteogenic differentiation of human bone marrow mesenchymal stem cells in a pathway involving Wnt/β-catenin signaling [13]. Extract of beet roots, which is widely used in folk medicine as wound healing medicine have been applied with culture of mesenchymal stem cells for tissue engineering [15]. Herbal medicine has been considered as an alternative due to various reasons including antibiotic overuse and misuse [4].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, many experiments have demonstrated that MSCs have the characteristics of self-renewal and are able to differentiate into adipocytes, osteoblasts, neurons, myoblasts, and endothelium. They have been discovered in muscles, umbilical cord blood, amniotic fluid, and other tissues, [ 36 ] and are potent therapeutic sources to repair damaged tissues, such as cardiac tissue, spinal cord injury, and complex perianal fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) first found in bone marrow can differentiate into osteoblasts, chondrocytes, adipocytes, myoblasts and other functional cells in vitro (12). According to related studies, Basso, Beattie and Bresnahan (BBB) score system confirms that the injection of bone marrow MSCs (BMSCs) in SCI rats can improve their motor function and accelerate motor recovery during spinal transplantation in mice with moderate SCI (13).…”
Section: Introductionmentioning
confidence: 99%